2021
DOI: 10.1002/jobm.202100241
|View full text |Cite
|
Sign up to set email alerts
|

Application of acid and heavy metal resistant bacteria from rat‐hole coal mines in bioremediation strategy

Abstract: The Gram-negative bacteria isolated from acid mine drainage (AMD) of rathole coal mines were found to be resistant to acidic conditions as well as Fe, Cd, and Cr. The minimum inhibitory concentration (MIC) and maximum bactericidal concentration (MBC) of iron, cadmium, and chromium against the isolates of Enterobacter huaxiensis KHED8 were 4000, 4096, and 256 mg/L, respectively, while the MIC and MBC of Fe, Cd, and Cr against two isolates (KH5M10 and KHCL12) of Serratia marcescens subsp. sakuensis isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…inaquosorum SK22 and Bacillus cereus SK44, isolated from rat-hole coal mines showed resistance to 100 mg/L of Fe and 1 mg/L of both Cd and Cr compared with the control strains of Bacillus subtilis MTCC 441 and Bacillus cereus MTCC 430. The same authors, in another study [ 158 ], aimed to profile the native bacterial isolates from a rat-hole coal mine for their bioprospection as bioremediating agents, and found that the minimum inhibitory concentration and maximum bactericidal concentration of Cd 2+ , Fe 2+ , and Cr 6+ against Enterobacter huaxiensis KHED8 were 4000, 4096, and 256 mg/L, respectively. Furthermore, E. huaxiensis KHED8 was able to remove 89%, 90%, and 82.45% of Fe 2+ , Cd 2+ , and Cr 6+ , respectively.…”
Section: Bioremediation Of Contaminated Sites By Native Microorganismsmentioning
confidence: 99%
“…inaquosorum SK22 and Bacillus cereus SK44, isolated from rat-hole coal mines showed resistance to 100 mg/L of Fe and 1 mg/L of both Cd and Cr compared with the control strains of Bacillus subtilis MTCC 441 and Bacillus cereus MTCC 430. The same authors, in another study [ 158 ], aimed to profile the native bacterial isolates from a rat-hole coal mine for their bioprospection as bioremediating agents, and found that the minimum inhibitory concentration and maximum bactericidal concentration of Cd 2+ , Fe 2+ , and Cr 6+ against Enterobacter huaxiensis KHED8 were 4000, 4096, and 256 mg/L, respectively. Furthermore, E. huaxiensis KHED8 was able to remove 89%, 90%, and 82.45% of Fe 2+ , Cd 2+ , and Cr 6+ , respectively.…”
Section: Bioremediation Of Contaminated Sites By Native Microorganismsmentioning
confidence: 99%
“…Many researchers have proposed several technologies categorized into active and passive treatment techniques (Bai et al, 2021;Vasquez et al, 2022). Examples of passive techniques are bioremediation, constructed wetlands, phytoremediation (Wibowo et al, 2023a;Wibowo et al, 2022b) and bioreactors (Ka-ot and Joshi, 2022;Thomas et al, 2022;Wang et al, 2021a), while the active techniques include neutralization, precipitation, adsorption, electrochemical treatment, and membrane technology (Angai et al, 2022;Bao et al, 2022;Lee et al, 2022b). Both techniques have advantages and disadvantages (Ighalo et al, 2022) .…”
Section: Introductionmentioning
confidence: 99%